Contribution of Peer Relations - Ode Yahyu Herliany Yusuf; Sitti Aziza Nur Hady; Hasriana Hasriana; Magfira Magfira; Selfianti Selfianti (CV. Rayyan Dwi Bharata, 2023)
The ability of social interaction requires a relationship between one individual and another individual who is involved in communication, including a reciprocal relationship between one another. The ability to behave socially needs to be possessed since the child is small as a foundation for the development of the child's ability to interact with the wider environment so that early childhood in kindergarten is a social being who needs the presence of other people in his life and has a strong desire to be accepted. by the group and to be able to join with peers.